Patient characteristics and analgesic efficacy of antiviral therapy in postherpetic neuralgia. (October 2019) - Lin, Yao-Tsung; Wang, Li-Kai; Hung, Kuo-Chuan; Wu, Zhi-Fu; Chang, Chia-Yu; Chen, Jen-Yin
Abstract: Postherpetic neuralgia (PHN) is the most common complication of shingles caused by reactivation of varicella zoster virus (VZV). Management of PHN is often suboptimal while using current conventional treatments. Antiviral therapy was used to reduce PHN-associated pain in two small trials which showed conflicting results. We hypothesize the analgesic efficacy of antiviral therapy on PHN is affected by patient characteristics including pathophysiology of the participants and serum vitamin D levels. Pathophysiology of PHN includes neuronal excitability and chronic VZV ganglionitis (persistent active VZV infection in ganglions). VZV-DNA positivity or a positive IgG coupled with a positive IgM indicates recent or current VZV infection. Positive VZV-DNA or IgG/IgM tests are used to confirm whether the patients experience chronic VZV ganglionitis. Antiviral therapy decreases pain in PHN patients with chronic VZV ganglionitis; whereas, antiviral therapy shows no effects in PHN patients with negative VZV-DNA or IgM. Vitamin D is a natural antiviral mediator. Studies show a high prevalence of vitamin D deficiency in hepatitis B/C virus-infected patients. Serum vitamin D levels and vitamin D supplementation are factors which affect the antiviral efficacy on hepatitis B/C virus infection. Serum 25-OHD levels of hospitalized patients with shingles were significantly lower compared to healthy controls. Accordingly, PHN patient may have a high prevalence of vitamin D deficiency which negatively affects the antiviral efficacy. Vitamin D supplementation may improve the antiviral efficacy on PHN. Future trials regarding antiviral therapy on PHN should consider patient characteristics and should be conducted among different subgroups of PHN patients.